Anemia and its Associated Factors Among Women of Reproductive Age in Horticulture Area - Yushananta, Prayudhy; Anggraini, Yetti; Ahyanti, Mei; Sariyanto, Iwan (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Anemia continues to be an important and widespread public health problem, so it must be addressed. About 1.74 (1.72-1.76) billion people worldwide suffer from anemia, especially children under five, women of reproductive age (WRA), and pregnant women. As many as 500 million WRA suffer from anemia; this will impact the loss of productivity due to decreased work capacity, cognitive impairment, susceptibility to infections, and increased risk of complications in pregnancy and childbirth. This study analyzes the risk factors for anemia in women of reproductive age (15-59) who work in horticultural agriculture. The study was conducted with a cross-sectional design involving 160 participants from three main centers of horticultural agriculture in West Lampung Regency. SPSS was used for Chi-square analysis, Odds Ratio, and Logistic Regression (alpha = 0.05). The results showed that the prevalence of anemia in women of reproductive age who worked in horticultural agriculture was 27.5%. The study also identified three risk factors for anemia: poor nutritional status (AOR = 24.53; 95% CI 5.59-107.70), lack of protein intake (AOR = 28.01; 95% CI 6.97- 112.52), and less intake of high iron vegetables (AOR = 6.13; 95% CI 1.79-21.01). Nutritional interventions should emphasize increasing protein, iron, and vitamins through improved diet, fortification efforts, and iron supplementation.Abstrak: Anemia masih terus menjadi masalah kesehatan masyarakat yang penting dan meluas, sehingga harus ditangani. Sekitar 1,74 (1,72-1,76) miliar penduduk dunia menderita anemia, terutama anak balita, wanita usia subur (WUS) dan wanita hamil. Sebanyak 500 juta WUS menderita anemia, iniakanberdampak pada hilangnya produktivitas karena penurunan kapasitas kerja, gangguan kognitif, dan kerentanan terhadap infeksi, serta meningkatkan risiko komplikasi kehamilan dan persalinan. Penelitian bertujuan menganalisis faktor risiko anemia pada wanita usia subur (15-59) yang bekerja pada pertanian hortikultura. Penelitian dilakukan dengan rancangan cross sectional, melibatkan 160 orang partisipan dari tiga sentra utama pertanian hortikultura di Kabupaten Lampung Barat. SPSS digunakan untuk analisis Chi-square, Odds Ratio, dan Logistic Regression (alpha=0,05). Hasil penelitian mendapatkan prevalensi anemia pada wanita usia subur yang bekerja pada pertanian hortikultura sebesar 27,5%. Penelitian juga mendapatkan tiga faktor risiko untuk anemia: status gizi yang kurang baik (AOR=24,53; 95%CI 5,59-107,70), kurang asupan protein (AOR=28,01; 95%CI 6,97-112,52), dan kurang asupan sayuran tinggi zat besi (AOR=6,13; 95%CI 1,79-21,01). Intervensi gizi harus menekankan pada peningkatan asupan protein, zat besi dan vitamin, baik melalui perbaikan menu makanan, upaya fortifikasi dan suplementasi tablet Fe.